Molecular imaging for the characterization of breast tumors. Issue 6 (June 2014) - Magometschnigg, Heinrich Florian; Helbich, Thomas; Brader, Peter; Abeyakoon, Oshaani; Baltzer, Pascal; Füger, Barbara; Wengert, Georg; Polanec, Stephan; Bickel, Hubert; Pinker, Katja
Abstract : Recently, molecular imaging, using various techniques, has been assessed for breast imaging. Molecular imaging aims to quantify and visualize biological, physiological, and pathological processes at the cellular and molecular levels to further elucidate the development and progression of breast cancer and the response to treatment. Molecular imaging enables the depiction of tumor morphology, as well as the assessment of functional and metabolic processes involved in cancer development at different levels. To date, molecular imaging techniques comprise both nuclear medicine and radiological techniques. This review aims to summarize the current and emerging functional and metabolic techniques for the molecular imaging of breast tumors.